Mental health care for rare disease in the UK - recommendations from a quantitative survey and multi-stakeholder workshop - Rosa Spencer-Tansley; Nick Meade; Farhana Ali; Amy Simpson; Amy Hunter (BMC, 2022)
Abstract Background Rare disease patients and carers report significant impacts on mental health but studies on UK populations have focussed on relatively few, specific conditions. Collectively rare conditions represent a substantial health burden, with an estimated 3.5 million affected individuals in the UK. Method We explored the impact on mental health of living with a rare condition, and experiences of health service support, through an online survey. The survey assessed the impact of specific experiences commonly reported by those affected by a rare condition through multiple choice questions and Likert scale items, and open text question boxes. Through a multi-stakeholder workshop that involved facilitated discussion of our findings with patients/carers, clinicians and a government advisor, we developed recommendations for policy and practice toward a more person-centred and integrated approach. Results Eligible responses came from 1231 patients and 564 carers. Due to their rare condition, the majority of respondents (> 90%) had felt worried/anxious; stressed; and /or low/depressed. Thirty-six percent of patients and 19% of carers had had suicidal thoughts. Challenges that are particular to rare conditions and which negatively affect mental health included limited knowledge of the condition amongst healthcare professionals (88%), and not being believed or taken seriously by them. Only 23% of respondents felt healthcare professionals considered mental and physical health as equally important. Almost half reported never having been asked about mental health by healthcare professionals. Our findings indicate that access to, and appropriateness of, professional psychological support needs to be improved. Peer group support is important but signposting is inadequate. Our recommendations are for healthcare professionals to be supported to effectively and sensitively recognise and address patients' and carers' mental health needs; and for service level coordination of care to integrate professional psychological support with rare disease services. Conclusion Living with a rare disease substantially impacts mental health. Many of the drivers of poor mental health reflect issues specific to managing rare conditions. To meet UK government commitments, there should be a focus on empowering healthcare professionals who treat rare disease patients and on integration of mental health support with rare disease services.